Visualizing the Expressive Use of Technology in the Design of Parametrically Generated Ecoenvelopes - Brakke, Aaron Paul; Velasco, Rodrigo (ARCC Conference Repository, 2014)
This paper illustrates how computational design has surfaced in the architectural discourse. One particular area of interest has been in parametric design. The authors argue against Parametricism, an avante garde movement which is limited to the issues of style and aesthetic fitness. Instead, an approach that uses parametric modelling, simulation and visualization in an iterative way to generate design solutions for complexities of contemporary design problems is favoured. The authors present a particular case study where parametric design is utilized in the development of a research project that looks for appropriate solutions for building envelopes in hot and humid climates. The process involved the selection of geometrically dependent parameters and their translation into variable fields, variable instances and range values. The parameters and the possible values were based on literature reviews and digital simulations (pre-evaluations) of different types, but categorized as functional, technological and environmental. Even though the project is ongoing, the generation and evaluation of the designs carried out as part of the present research have already yielded results that can guide designers towards informed solutions of the problem studied. More importantly, the study presents a methodology that, understood as part of so many other similar proposals, can assist in the construction of new and more efficient digitally driven design and research processes.